PERUBAHAN CITRA PEREMPUAN DALAM IKLAN BIR DI JEPANG PADA AWAL DAN AKHIR TAHUN 1930-AN - PUTRI, DESITA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Women in the media are often shown in a negative through the potrayal displayed in public spaces. In the mass media, the analysis of the potrayal of women in the mainstream media and the creation of alternatives to the feminist view of women in the media became an important project in feminist theory. Potrayal of women in the media are called feminists as a major source for the production of patriarchal social relations in general.In this study, beer advertisements at the beginning and the end of 1930 was chosen to see the changes in Japan's potrayal of women in the mass media. Paul Ricoeur's hermeneutic theory is used to dissect the advertising of the socio-historical, which is an essential element for the writer to find a change of potrayal in the ad. Through the five stages of Paul Ricoeur's hermeneutic theory, namely dialogue with the reader, the author reveals his interpretation of the advertisement is based on feminism and women's point of view in the media.The results revealed that of the four studied advertisements, two ads from early 1930s and two advertisements from the late 1930s showed a change in the potrayal of women. Such changes appear not only on how women appear physically, ie with minimal clothing and erotic, but also of the role of women themselves. The role of women in these advertisements in the late 1930s is much better than the role of women featured in advertisements in the early 1930s.In addition, for further research suggested that Japanese learners more critical of the advertisements in the Japanese media, the advertisements that appear in the mass media show women potrayals to a certain extent. Keywords: Japanese beer advertisements, hermeneutic, feminism, women in the media